2023
DOI: 10.1093/mnras/stad399
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the high-mass binary black hole population from stable mass transfer and super-Eddington accretion in bpass

Abstract: With the remarkable success of the LVK consortium in detecting binary black hole mergers, it has become possible to use the population properties to constrain our understanding of the progenitor stars’ evolution. The most striking features of the observed primary black hole mass distributions are the extended tail up to 100M⊙ and an excess of masses at 35M⊙. Currently, isolated binary population synthesis have difficulty explaining these features. Using the well-tested bpass detailed stellar binary evolution m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 148 publications
1
3
0
Order By: Relevance
“…In particular, van Son et al (2022b) found that more massive BHs are formed exclusively by the stable mass transfer channel, while the common envelope channel dominates the formation of lower-mass systems. This result was confirmed by Belczynski et al (2022) and Briel et al (2023). Given the distinct delay time distributions of these two channels (Figure 1), this implies a mass dependence of the delay time distribution.…”
Section: Discussion On Simplifying Assumptionssupporting
confidence: 62%
“…In particular, van Son et al (2022b) found that more massive BHs are formed exclusively by the stable mass transfer channel, while the common envelope channel dominates the formation of lower-mass systems. This result was confirmed by Belczynski et al (2022) and Briel et al (2023). Given the distinct delay time distributions of these two channels (Figure 1), this implies a mass dependence of the delay time distribution.…”
Section: Discussion On Simplifying Assumptionssupporting
confidence: 62%
“…There are additional uncertainties in binary population synthesis that we did not explore in this work. For example, it has been proposed that super-Eddington accretion onto the first-born BH can dramatically increase its mass and lead to more asymmetric systems (Bavera et al 2021;Briel et al 2022;Zevin & Bavera 2022). However, such conservative mass transfer is not as efficient as nonconservative mass transfer in shrinking the orbit, and so this scenario may not contribute much to the merger rate.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation, generalrelativistic, and magneto-hydrodynamics simulation of a supercritical accretion disk around BHs (e.g., S ądowski & Narayan 2016) suggest that the accretion rate may significantly exceed the Eddington limit. This possibility has been explored in the context of BH high-mass X-ray binaries (Moreno Méndez et al 2008;Qin et al 2022) and coalescing binary BH populations (e.g., Bavera et al 2021;Briel et al 2023). However, the effect of super-Eddington accretion on the formation and the properties of merging NSBH, and especially the probability of being accompanied by EMCs, is less well studied.…”
Section: Uncertainties In Stellar and Binary Physicsmentioning
confidence: 99%